1994
DOI: 10.1007/bf02221593
|View full text |Cite
|
Sign up to set email alerts
|

Spinal bone mineral density changes following halo vest immobilization for cervical trauma

Abstract: In this prospective study we followed the bone mineral density (BMD) changes of the injured cervical spine immobilized with the halo vest. In order to define the natural history of cancellous vertebral bone loss and restoration, dual-energy densitometry was used on each of ten selected cervical spines in the lateral view (1) immediately after the application of the device, (2) at the end of the treatment and (3) 3 months after the removal of the halo vest. The halo vest produces local osteoporosis in the immob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In the cervical spine, Korovessis et al prospectively demonstrated loss of bone mineral density in patients placed in a halo vest for 3 months in the treatment of cervical fractures. 12 Together, these studies provide evidence that traction across the spine or extremities for extended periods leads to the development of local disuse osteoporosis.…”
Section: Discussionmentioning
confidence: 98%
“…In the cervical spine, Korovessis et al prospectively demonstrated loss of bone mineral density in patients placed in a halo vest for 3 months in the treatment of cervical fractures. 12 Together, these studies provide evidence that traction across the spine or extremities for extended periods leads to the development of local disuse osteoporosis.…”
Section: Discussionmentioning
confidence: 98%
“…Dual energy X-ray absorptiometry (DEXA) is a noninvasive method of measuring bone mineral density (BMD), and has been found to be an adequate procedure for evaluating the natural history of osteoporosis of the spine and femoral neck [1,3,8,10,11,16]. The versatility, precision and accuracy of the latest techniques make measurement of the effect of implantation of a total hip arthroplasty (THA) on the bone mass increasingly feasible [1,4,5,6,7,9,10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…29 In addition, DXA measurements of the cervical spine are not routinely performed 30 and are technically challenging due to projection artifacts, especially in the lower cervical spine. 8,18 Given these difficulties, BMD measurements were performed using QCT in this study. QCT is an alternative to DXA and is less prone to degenerative changes in the spine.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for spinal BMD loss after fusion surgery are not yet fully understood and previous authors have tried to provide possible explanations for this phenomenon, including immobilization, 2,3,5,7,8 altered mechanics associated with arthrodesis, 3,4,6 and local or systemic inflammation following the surgical procedure. [9][10][11] Besides obvious anatomical and biomechanical differences, different degrees of surgical insult as well as the different postoperative management might possibly contribute to the discrepancy between the small cervical BMD decrease following ACDF observed in this study compared to the previously reported extensive lumbar BMD loss following lumbar fusions.…”
Section: This Is Surprising Since Cervical Fusion Patients Oftentimes...mentioning
confidence: 99%